2018
DOI: 10.1111/1759-7714.12630
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides from a Codonopsis pilosula endophyte activate macrophages and inhibit cancer cell proliferation and migration

Abstract: BackgroundExopolysaccharides with structural diversity have shown wide applications in biomaterial, food, and pharmaceutical industries. Herein, we isolated an endophytic strain, 14‐DS‐1, from the traditional medicinal plant Codonopsis pilosula to elucidate the characteristics and anti‐cancer activities of purified exopolysaccharides.MethodsHPLC and GC‐MS were conducted to purify and characterize the exopolysaccharides isolated from 14‐DS‐1. Quantitative RT‐PCR, cell migration assays, immunofluorescence staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 77 publications
1
31
0
Order By: Relevance
“…[21][22][23][24][25][26][27][28] In vivo and in vitro studies have shown that these bioactive components may augment the immune response, 27,28 enhance antioxidant abilities, 29,30 induce apoptotic pathways, 31 and suppress cancer cell migration. 32 Moreover, extractions of S. glabra and S. coicis may inhibit the activation of EBV 33 by eliminating free radicals, inducing the functional maturation of dendritic cells, and activating macrophages. 32,[34][35][36][37][38] M. officinalis, the species with the lowest OR, may regulate lymphocyte apoptosis, 39 mediate macrophage activation, 40 and suppress NF-κβ pathways.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28] In vivo and in vitro studies have shown that these bioactive components may augment the immune response, 27,28 enhance antioxidant abilities, 29,30 induce apoptotic pathways, 31 and suppress cancer cell migration. 32 Moreover, extractions of S. glabra and S. coicis may inhibit the activation of EBV 33 by eliminating free radicals, inducing the functional maturation of dendritic cells, and activating macrophages. 32,[34][35][36][37][38] M. officinalis, the species with the lowest OR, may regulate lymphocyte apoptosis, 39 mediate macrophage activation, 40 and suppress NF-κβ pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The wave swing is spread by the antirelaxation coordination but the mechanism of adjusting the synchronous swing of multiple cilia is not clear. In addition, the effectiveness of MCC is affected by a diversity of factors, including cilia numbers and their structure, humidity, temperature, age, pathogens, and environmental stimuli …”
Section: Structure and Function Of Airway Ciliamentioning
confidence: 99%
“…Compared with normal cells, tumor cells, especially malignant tumors, exhibit abnormal movement and migration capabilities, rapid cell division, and cytoskeletal abnormalities . At the same time, existing studies have shown that persistent inflammation can also trigger and exacerbate malignant tumors .…”
Section: Discussionmentioning
confidence: 99%